Влияние азота на накопление фукоксантина диатомовой водорослью Cylindrotheca closterium (Ehrenb.) Reimann et Lewin - Рябушко, В.И.; Железнова, С.Н.; Нехорошев, М.В. (Альгология, 2017)
Исследовано влияние азота в питательной среде на накопление фукоксантина (Fc) диатомовой водорослью Cylindrotheca closterium. Содержание Fc в биомассе микроводоросли определяли при переходе на стационарную фазу роста. Увеличение концентрации азота в питательной среде F/2 способствует накоплению фукоксантина в культуре. Установлено, что при концентрации нитрата натрия 225—300 мг·л.⁻¹ в питательной среде количество фукоксантина в сухой биомассе С. closterium достигает 15 мг·г.⁻¹. При этом максимальная концентрация клеток составляет более 2 млн кл.·мл.⁻¹, а среднесуточная удельная скорость роста — 0,21 сут.⁻¹. Использование питательной среды с высокой концентрацией азота позволяет получать культуру C. closterium, обогащенную биологически активным веществом фукоксантин. Поэтому диатомовую водоросль Cylindrotheca closterium можно рассматривать как перспективный объект в биотехнологии. The effect of inorganic nitrogen content in the culture medium on accumulation of fucoxanthin (Fc) in the diatom Cylindrotheca closterium was studied. The Fc content in the biomass of the microalgae is determined in the transition to the stationary growth phase. Increase of the concentration of nitrogen in the medium F/2 promotes accumulation of fucoxanthin in the culture. With the concentration of sodium nitrate 225–300 mg · L.⁻¹ in the medium, the concentration of fucoxanthin in dry biomass of C. closterium is found to reach 15 mg · g.⁻¹. The maximum cell concentration is above 2·106 cells · mL.⁻¹ and the average specific growth rate is 0.21 day.⁻¹. Use of nutrient medium with high concentration of nitrogen allows obtaining the culture of C. closterium enriched with the biologically active substance fucoxanthin. Consequently, the diatom Cylindrotheca closterium can be regarded as a promising object in biotechnology.